Níveis de lisina em dietas para reprodutores de Rhamdia voulezi em tanques-rede - Diemer, Odair [UNESP] (2014)
The aim was to evaluate the levels of lysine in diets to breeding of Rhamdia voulezi in cages evaluating the productive, reproductive performance, hormonal characteristics, organosomatic indices and amino acid incorporation in oocytes and in the carcass in. Four hundred fish were used with an average initial weight of 35.18 ± 0.25g, distributed in a randomized design with four treatments and four replications in 16 cages with 25 fish each. The treatments consisted of four diets designed to contain levels of total lysine of 1.20; 1.40; 1.60 and 1.80% with 30% crude protein and 3,500 kcal kg-1 digestible energy. After fed for 185 days it was randomly selected 18 males that liberated semen under mild compression of the abdomen and 18 females who had rounded abdomen, swollen and reddish urogenital papilla, and taken to the laboratory where they were weighed, measured, submitted to hypophysation (with crude carp pituitary extract (EHC)) at a dose of 2.5 mg.kg-1 in males and 5.5 mg.kg-1 for females. After 240 thermal units accumulated, the semen was collected for fertilization and evaluation of the following parameters: semen volume, duration and rate of sperm motility, sperm survival index, sperm concentration, percentage of normal sperm, pH and osmolarity. At the same time, the oocyties was colellected and divided into portions: Gilson solution (oocyte diameter), frozen (amino acid analysis) and the remainder in fertilized with pre-analyzed semen and willing conical incubators (20L) for measurement of reproductive parameters. Then, the blood was collected (analysis of cortisol, estradiol and testosterone), after it they were sacrificed by dislocation of the cervical spine, dissected, where the ovaries, testicles, liver, fat and viscera were removed, weighed and estimated the respective organosomatic indices. Carcasses were dried for analysis of amino acids. In males was verified effect (p<0.05) for the final weight, weight gain, feed ...